Employing e-portfolio based learning in improving self-efficacy of student’s speaking ability - I Putu Yoga Laksana; Ni Nyoman Yuliantini; Ni Ketut Suciani; I Putu Yoga Purandina; Gary P. Boyce (Journal of Applied Studies in Language, 2021)
This research aimed at knowing the effectiveness of online learning design with an e-portfolio approach in increasing self-efficacy in speaking ability. Seventy-seven students were involved in this study. They are in the second semester of a vocational college in Business Administration Department in the academic year 2020/2021. This research is experimental research with implementing paired samples t-test as the measurement tool in knowing the effectiveness of e-portfolio based learning by finding the t score and the sig value before and after the implementation of the teaching method. The result of this study showed that e-portfolio based learning had a significant effect on the student's self-efficacy in their speaking ability. It was indicated by the value of the sig and t result from paired samples t-test analysis which was showed 0.000 as the sig value and -20.551 as the t count. The result of sig value which is below 0.05 and the t-count which is above t-table were clear indicators to argue that e-portfolio significantly impacted the student's self-efficacy in speaking ability. In this case, the variables of self-efficacy in speaking ability were improved significantly by the implementation of e-portfolio based learning. Even the implementation of e-portfolio brings many positive impacts on the students, some limitations lie on this method implementation. The limitation of this method lies in the time execution and the number of students who are taught by the lecturer.